Environmental Policies and Productivity Growth A Critical Review of Empirical Findings - Koźluk, Tomasz (OECD Economics Department Working Papers, 2013)
The economic effects of environmental policies are of central interest to policymakers. The traditional approach sees environmental policies as a burden on economic activity, at least in the short to medium term, as they raise costs without increasing output and restrict the set of production technologies and outputs. In contrast, the Porter Hypothesis claims that well-designed environmental policies can provide a 'free lunch' - encouraging innovation, bringing about gains in profitability and productivity that can outweigh the costs of the policy. This paper reviews the empirical evidence on the link between environmental policy stringency and productivity growth, and the various channels through which such effects can take place. The results are ambiguous, in particular as many of the studies are fragile and context-specific, impeding the generalisation of conclusions. Practical problems related to data, measurement and estimation strategies are discussed, leading to suggestions how they can be addressed in future research. These include: improving the measurement of environmental policy stringency; investigating into effects of different types of instruments and details of instrument design; exploiting cross-country variation; and the complementary use of different levels of aggregation